2005
DOI: 10.1130/b25591.1
|View full text |Cite
|
Sign up to set email alerts
|

3D seismic reflection mapping of the Silverpit multi-ringed crater, North Sea

Abstract: The fi rst comprehensive mapping of the Silverpit multi-ringed crater is presented, based on fi ve adjoining 3D seismic surveys that together provide 78% (216 km 2 ) areal coverage of the structure with spatial and depth sampling of ~10 m. The top Cretaceous surface shows an excavated crater 3 km in diameter surrounded by 10-15 concentric ring structures out to a radius of 9.4 km. Seismic sequence stratigraphy and drilled wells indicate the lower age bound is a disconformity spanning 74-54 Ma. The upper bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
2
35
2
Order By: Relevance
“…First, there is a candidate impact crater (the Silverpit structure) imaged on 3D seismic data in the Upper Cretaceous section, buried by 500 m of sediment ( Fig. 1a and b; Stewart & Allen 2005). Second, although several impact craters are predicted, including three in the size range of the Silverpit structure, Silverpit is the only candidate impact structure described to date, suggesting that several more remain to be discovered.…”
Section: North Sea Basinmentioning
confidence: 93%
See 2 more Smart Citations
“…First, there is a candidate impact crater (the Silverpit structure) imaged on 3D seismic data in the Upper Cretaceous section, buried by 500 m of sediment ( Fig. 1a and b; Stewart & Allen 2005). Second, although several impact craters are predicted, including three in the size range of the Silverpit structure, Silverpit is the only candidate impact structure described to date, suggesting that several more remain to be discovered.…”
Section: North Sea Basinmentioning
confidence: 93%
“…(a) Seismic reflection cross-section of Silverpit structure, North Sea (Stewart & Allen 2005). (b) Map view of Silverpit structure, North Sea (Stewart & Allen 2005). (c) Seismic reflection 3D cube of Praia Grande structure, Santos Basin, Brazil (Correia et al 2005).…”
Section: Earth Impact Databasementioning
confidence: 98%
See 1 more Smart Citation
“…Within of the ring fault system, the Sharawra and Tawil formations are folded into a gentle ring syncline with minor concentric, spiral and low angle faults (Figures 4,5;Janjou et al, 1997). Faults with spiral trend in planview can occur in ring structures that involve centripetal movement of material, see discussion in Stewart & Allen, (2005). Moving from the synclinal hinge towards the center of the ring, structural dips increase towards the base of the Sharawra Formation, locally reaching 45 degrees at the contact with the Qusaiba Formation and always dipping away from the center of the ring thus defining a dome at top Qusaiba level.…”
Section: Jabal Rayah -Descriptionmentioning
confidence: 97%
“…The structures as delineated by seismic means depend on many variables such as the volume and extent of melt sheets, the amount of brecciation or damage, and the size of the structure. The number of seismological studies of impact structures has grown substantially over the last few years with studies at scales ranging from hundreds of kilometers over large impact structures such as Chicxulub in Mexico (Morgan et al 2000) and Sudbury (Wu et al 1995;Boerner et al 2000) to smaller structures such as the Mjølnir structure, which is 40 km in diameter (Dypvik et al 2004) in the Barents Sea, and the buried (but not yet confirmed to be an impact) Silverpit structure, which is ~10 km in diameter, that was well resolved in 3-D seismic images (Stewart and Allen 2005). The age range for these seismically studied structures extends from the 2.02 Gyr old Vredefort-Witwatersrand structure of South Africa (cf.…”
Section: Seismological Investigations Of Impact Structuresmentioning
confidence: 99%